The “No Viral, No Justice” Phenomenon and Its Implications for Due Process in the Legal System - Putri Setiawati Nusi (Eastasouth Institute, 2026)
The “No Viral No Justice” phenomenon reflects a shift in the relationship between society, social media, and the law enforcement system in the digital age. This study aims to analyze the implications of this phenomenon on the application of the due process of law principle within the legal system. The method used is normative legal research with a conceptual and statutory approach, supported by qualitative analysis of empirical practices. The research findings indicate that virality on social media significantly influences the response of law enforcement officials, thereby creating disparities in case handling and potentially undermining the principles of equality before the law and the presumption of innocence. Furthermore, public opinion pressure can interfere with the independence of legal proceedings and shift the orientation of justice from procedural to perceptual. Although social media functions as an effective tool for social control, the dominance of unverified information risks undermining the integrity of the judicial system. This study concludes that this phenomenon poses a serious challenge to the rule of law and demands strengthened regulations, greater professionalism among officials, and improved public legal literacy to maintain a balance between transparency and judicial independence.